Organizational change capability and ambidexterity: The mediating role of innovativeness and responsiveness - Anita Talaja; Vlatka Škokić; Nikol Mise (Cogent Business & Management, 2023)
AbstractThis study aims to investigate whether organizational change capability (OCC) enables firms’ ambidexterity (explorative innovativeness and exploitative responsiveness) and results in above-average performance. Besides testing whether ambidexterity is possible, the study also investigates how it can be achieved by testing the role of mediators in the relationship between OCC and a firm’s performance. The study surveyed suppliers of a large Croatian firm from the construction industry. A total of 160 usable surveys were collected and data analysis was conducted using partial least squares structural equation modeling. Our study confirms the positive effect of OCC on a firm’s responsiveness and innovativeness, while also demonstrating that OCC has a positive impact on a firm’s performance. In addition, the results empirically show for the first time that OCC and innovativeness have a positive impact on a firm’s responsiveness. This study contributes to the understanding of the OCC construct by linking it to ambidexterity and investigating the role of mediators in the relationship between OCC and a firm’s performance.